Digital Payment Systems, Behavioral Finance, and Personal Financial Management: A Perspective on Millennials and Gen Z - Abdul Manap; Zurlina Lubis; Riah Ukur Br Ginting; Zainuddin Zainuddin; Saut Pane; Arko Pujadi (Journal of Innovative and Creativity (Joecy), 2026)
The expansion of digital payment platforms has fundamentally altered the financial habits of younger demographics, specifically Millennials and Generation Z (Gen Z). Although these fintech solutions provide unparalleled convenience, their pervasive use raises critical questions regarding consumer behavior and long-term financial stability. This study investigates the interplay between behavioral biases, digital payment utilization, and personal financial planning among young consumers. Employing a quantitative methodology, data gathered from 320 active digital payment users were evaluated using Partial Least Squares Structural Equation Modeling (PLS-SEM) to assess direct, indirect, and moderating dynamics. The empirical results demonstrate that behavioral biases negatively impact financial planning while driving digital payment adoption. Concurrently, reliance on digital payments exerts a negative direct effect on financial planning and acts as a partial mediator in the model. Notably, multi-group analysis indicates that these detrimental effects are more pronounced within Gen Z than Millennials. These insights enrich the behavioral finance and fintech literature by revealing the psychological drivers behind digital consumption, underscoring the urgent need for targeted financial literacy initiatives and intentional fintech design features that foster disciplined spending.